PENENTUAN MUSIM TANAM PADI SAWAH MENGGUNAKAN DATA TIME SERIES CURAH HUJAN DI DAS LIMBOTO BONE BOLANGO - Romansah Wumu; F.V. Astrolabe Sian Prasetya (Politeknik Pertanian Negeri Samarinda, 2021)
Paddy is a staple food for most Indonesian people. A number of efforts were made to maintain the availability of paddy in the country. One of these efforts is to determine the beginning of the paddy planting season, especially lowland paddy in order to get maximum results and minimize crop failure. This study aims to determine the beginning of the growing season in the Limboto Bone Bolango watershed area. The beginning of the rainy season is the best time to be the beginning of the paddy planting season which requires sufficient irrigation in the vegetative phase. The data used in this study is rainfall time series data which is processed from TRMM 3B43 data: Monthly Precipitation Estimates (TRMM/3B43V7) and ERA5-Land monthly averaged - ECMWF climate reanalysis (ECMWF/ERA5_LAND/MONTHLY). Based on the time series data, the beginning of the rainy season is in February (DOY > 60) and October (DOY > 273). Based on this, it is expected that farmers in the Limboto Bone Bolango watershed can start the planting season in February and October.